2003
DOI: 10.1080/02643290244000211
|View full text |Cite
|
Sign up to set email alerts
|

Do Semantic Categories Activate Distinct Cortical Regions? Evidence for a Distributed Neural Semantic System

Abstract: A key issue in cognitive neuroscience concerns the neural representation of conceptual knowledge. Currently, debate focuses around the issue of whether there are neural regions specialised for the processing of specific semantic attributes or categories, or whether concepts are represented in an undifferentiated neural system. Neuropsychological studies of patients with selective semantic deficits and previous neuroimaging studies do not unequivocally support either account. We carried out a PET study to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
1
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 62 publications
5
47
1
1
Order By: Relevance
“…In fact, this part of the left middle temporal gyrus has been associated with the semantic network by both functional brain imaging (Chao, Haxby, & Martin, 1999;Buchel, Price, & Friston, 1998;Vandenberghe, Price, Wise, Josephs, & Frackowiak, 1996) and neuropsychological studies (Chertkow, Bub, Deaudon, & Whitehead, 1997). More recent work further suggested that the same region is invariably active during semantic judgment of objects irrespective of their categories (Tyler et al, 2003). Using fMRI, Thompson-Schill, D'Esposito, and Kan. (1999) also observed activation reduction of the left inferolateral temporal cortex associated with the repeated retrieval of semantic knowledge.…”
Section: Cross-script Priming In the Left Lateral Temporal Cortexmentioning
confidence: 88%
“…In fact, this part of the left middle temporal gyrus has been associated with the semantic network by both functional brain imaging (Chao, Haxby, & Martin, 1999;Buchel, Price, & Friston, 1998;Vandenberghe, Price, Wise, Josephs, & Frackowiak, 1996) and neuropsychological studies (Chertkow, Bub, Deaudon, & Whitehead, 1997). More recent work further suggested that the same region is invariably active during semantic judgment of objects irrespective of their categories (Tyler et al, 2003). Using fMRI, Thompson-Schill, D'Esposito, and Kan. (1999) also observed activation reduction of the left inferolateral temporal cortex associated with the repeated retrieval of semantic knowledge.…”
Section: Cross-script Priming In the Left Lateral Temporal Cortexmentioning
confidence: 88%
“…Posterior regions of the ventral temporal lobe are routinely found to be active during visual object processing (Haxby et al, 2001;Grill-Spector et al, 1998;Malach et al, 1995), and these same regions are implicated in processing the semantic information about objects (Bright, Moss, & Tyler, 2004;Tyler et al, 2003;Chao et al, 1999). The neurons in these regions have been found to respond to moderately complex information about an object (Tanaka, 1996;Kobatake & Tanaka, 1994), whereas whole objects are represented through distributed patches of neural activation (Tsunoda, Yamane, Nishizaki, & Tanifuji, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The neural infrastructure that supports this key cognitive function has been extensively investigated in nonhuman primates, resulting in a well-developed model of hierarchically organized object processing in ventral occipito-temporal cortex (Felleman & Van Essen, 1991;Ungerleider & Mishkin, 1982) that also supports the semantic processing of visual objects (Moss, Rodd, Stamatakis, Bright, & Tyler, 2005;Tyler et al, 2003Tyler et al, , 2004Chao, Haxby, & Martin, 1999). Although this research has been key in identifying the neural architecture that supports the recognition of visual inputs as meaningful objects, a comprehensive model of the neural mechanisms involved in processing meaningful objects requires the characterization of dynamic interactions along the ventral stream.…”
Section: Introductionmentioning
confidence: 99%
“…Neuropsychological (21,22) and functional brain imaging (23,24) studies converge to suggest that this region is associated with amodal, conceptual-level representations. Our finding thus suggests the existence of another distinct component of cross-script priming that is mediated by the activation of semantic knowledge.…”
Section: Discussionmentioning
confidence: 99%